Improving calcium bioavailability from fish bone waste: the role of sodium hydroxide in bio‑calcium extraction from tilapia (Oreochromis niloticus) bones - Theeraphol Senphan; Natthapong Mungmueang; Vachira Choommongkol; Chodsana Sriket; Hideki Kishimura; Phanat Kittiphattanabawon; Soottawat Benjakul (Food Chemistry X, 2025)
) bones. Tilapia bones were treated with 0.5 M, 1 M, and 2 M NaOH solutions for 30 min compared to untreated controls. Increasing NaOH concentrations decreased yield while improving brightness, ash content, and calcium bioavailability. The 2 M NaOH treatment produced bio‑calcium with highest calcium bioavailability (8.57 %), surpassing both control (7.26 %) and commercial calcium carbonate (0.72 %) by 12-fold. Higher NaOH concentrations reduced moisture, protein, and fat contents while increasing hydroxyproline and decreasing lipid oxidation. SEM showed smoother surfaces with homogeneous pores in 2 M NaOH-treated samples. ATR-FTIR and EDS confirmed consistent hydroxyapatite structure. This optimization provides a sustainable approach for converting fish waste into high-bioavailability calcium supplements, supporting circular economy in aquaculture while addressing global calcium deficiency.
Keywords: Protein Hydrolysis and Bioactive Peptides; Collagen: Extraction and Characterization; Calcium Carbonate Crystallization and Inhibition